AN OVERVIEW OF THE CENTRAL AMERICAN INTEGRATION SYSTEM - Ibrahim, Sheriff Ghali; Idagu, Adie Edward; Bibi F, Farouk Ibrahim (International Journal of Research -GRANTHAALAYAH, 2017)
The paper examines the formation and development of the Central American Integration System (SICA) and provides some of the strengths and weaknesses of the organization. From the application of secondary methodology, findings show that, the organization has been stable since formation. The paper concludes that, the organization has a lot to learn from other integration systems of the world to strengthen its own within the Central American region. The paper also recommends that, for SICA to achieve its set objectives all hands must be on desk in terms of total commitment by member states. The system should pay adequate attention to the economic aspect of the integration in order to benefit the member nations.